Vibrational Investigations of Silver-Doped Hydroxyapatite with Antibacterial Properties - Carmen Steluta Ciobanu; Simona Liliana Iconaru; Phillippe Le Coustumer; Daniela Predoi (Journal of Spectroscopy)
Silver-doped hydroxyapatite (Ag:HAp) was obtained by coprecipitation method. Transmission electron microscopy (TEM), infrared, and Raman analysis confirmed the development of Ag:HAp with good crystal structure. Transmission electron microscopy analysis showed an uniform ellipsoidal morphology with particles from 5 nm to 15 nm. The main vibrational bands characteristic to HAp were identified. The bands assigned to phosphate vibrational group were highlighted in infrared and Raman spectra. The most intense peak Raman spectrum is the narrow band observed at 960 cm−1. In this article Ag:HAp-NPs were also evaluated for their antimicrobial activities against gram-positive, gram-negative, and fungal strains. The specific antimicrobial activity revealed by the qualitative assay demonstrates that our compounds are interacting differently with the microbial targets.